Sufficiency Economy Philosophy: From the Buddhist Notion to Survival in Covid-19 Pandemic Crisis - et. al., Phrakhrusatugitgosol, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper's purposes were 1) to present the principle and justification of sufficiency economy, 2) to study the Buddhist notion in the sufficiency economy, and 3) to examine the values of the sufficiency economy for survival in the Covid-19 pandemic crisis from the Buddhist viewpoint. This paper used documents from Buddhist texts and modern texts. The contents analysis was used. The result indicated that the principle and justification of sufficiency economy found that the central concept of sufficiency economy philosophy is to guide the existence and practice or drive the country’s development to prosper stably and sustainably in various dimensions, which has changed. The result is a balanced development in all aspects. It is ready for economic change, society, environment, and culture, 2) the Buddhist notion in the sufficiency economy found that the sufficiency economy principle is directly related to the principles of the Middle Path in Buddhist teaching, which there are eight factors emphasize the refrain from the wrong occupation and provide a good faith occupation, 3) the value of the sufficiency economy for survival in Covid-19 pandemic from the Buddhist viewpoint found that the principle helps people to live their lives: be conscious of living during the COVID-19 pandemic by realizing the value of life. Therefore, Buddhism doesn’t focus on how much wealth we have, but it focuses on the right approach to property acquisition. Therefore, when we live in this crisis, we should live with self-sufficiency, protection, and rationality.